DIAMETER INCREMENT ESTIMATIONS OF Pinus brutia Ten. FORESTS STAND OF DUHOK GOVERNORATE, KURDISTAN REGION, IRAQ - Younis, Abdulaziz Jameel; Salih, Tariq Kurko (Science Journal of University of Zakho, 2025)
Pinus brutia Ten., a native eastern Mediterranean conifer, is prominent in northern Iraq and has enormous importance in the stability of ecosystems, biodiversity, and landscape protection. This study was conducted on Calabrian pine populations sampled from three ecologically differentiated sites in Duhok Province, Kurdistan Region, Iraq. Fifteen trees were selected, five per site, four of which will be used in a model calibration and one will be used for validation. Partial stem analysis was conducted by extracting cross-sections at breast height diameter. Despite the small sample size, the dataset provided sufficient observations for reliable statistical modeling. A systematic model selection framework was employed, incorporating tests of model assumptions, goodness of fit metrics, residual diagnostics, the Salih index to enhance the precision of Ohtomo’s test, R² interpretation, the Furnival index, and the Bias percent test. Allometric regression models were developed using STATGRAPHICS Centurion 19 software, and both homogeneous and heterogeneous forms were assessed. A t-test confirmed the reliability of the calibration models. Site-specific equations were derived based on the best-fitting regression forms: a curvilinear model was selected for both Zawita (Di = 6.2 − 1.2119 × ln(D)) and Atrush (Di = 14.8 − 2.8561 × ln(D)), while a square root transformation yielded the best fit at Belkef (Di = 14.1 − 1.7501 × √D)